Modified Masquelet technique using allogeneic umbilical cord-derived mesenchymal stem cells for infected non-union femoral shaft fracture with a 12 cm bone defect: A case report - Dilogo, Ismail Hadisoebroto (Int J Surg Case Rep, 2017)
INTRODUCTION: Non-union due to large bone loss often causes significant long-term morbidity. We incorporate the use of allogeneic umbilical cord-derived mesenchymal stem cells (UC-MSCs) as part of the diamond concept of regenerative medicine in a case of infected non-union fracture. PRESENTATION OF CASE: We reported a 54-year-old female patient presenting with pain on the right thigh. She was previously diagnosed with a closed fracture of the right femoral shaft and underwent four surgeries before finally being referred to Dr. Cipto Mangunkusumo General Hospital with infected non-union of the right femoral shaft. The patient was treated with a combination of UC-MSCs, bone morphogenetic protein-2 (BMP-2), Hydroxyapatite (HA), and mechanical stabilization using Masquelet Technique. The combination of allogeneic MSCs, BMP2, HA, and Masquelet Technique was successful in creating new bone with no apparent side effects. DISCUSSION: Bone loss might be caused by external factors (true defects), or structural loss of the existing bone. The combination of allogeneic UC-MSCs, BMP-2, HA and an induced membrane technique pioneered by Masquelet allowed for faster regeneration process and more optimal bone healing. This paper aims to assess and compare the result of such procedures with the previous four surgeries done to the patient, which did not yield satisfactory results. CONCLUSION: The application of allogeneic UC-MSC, BMP-2, HA and Masquelet technique as proposed in the diamond concept is a viable method in treating critical-sized bone defect and provides an effective way to overcome non-union caused by large defect.